2014
DOI: 10.1103/physreve.89.012902
|View full text |Cite
|
Sign up to set email alerts
|

First-harmonic approximation in nonlinear chirped-driven oscillators

Abstract: Nonlinear classical oscillators can be excited to high energies by a weak driving field provided the drive frequency is properly chirped. This process is known as autoresonance (AR). We find that for a large class of oscillators, it is sufficient to consider only the first harmonic of the motion when studying AR, even when the dynamics is highly nonlinear. The first harmonic approximation is also used to relate AR in an asymmetric potential to AR in a "frequency equivalent" symmetric potential and to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…If an inconclusive result is obtained, the state of the system is always the same regardless of the input. This case naturally appears in the embedding scheme when the ancilla has only one level [19]. This is consistent with the fact that no information can be encoded in a single quantum level.…”
Section: Singular Value Degeneracysupporting
confidence: 74%
See 1 more Smart Citation
“…If an inconclusive result is obtained, the state of the system is always the same regardless of the input. This case naturally appears in the embedding scheme when the ancilla has only one level [19]. This is consistent with the fact that no information can be encoded in a single quantum level.…”
Section: Singular Value Degeneracysupporting
confidence: 74%
“…Positive K operators have a special property. In [19] it was shown that the positivity is a necessary condition for minimizing the time-energy resources needed for unitary embedding of the desired USD. Note that if K is not positive, it can be made positive by applying a unitary from the left.…”
Section: Special Unitary Transformationsmentioning
confidence: 99%
“…and as a result further USD is possible. However in [35] there is an argument that explains why this is impossible.…”
Section: Usd Povm Results Can Be Reproduced By a Lossy Coherent Evolu...mentioning
confidence: 99%
“…Otherwise, by controlling the signal amplification, the detection probability can be effectively increased. A lossy evolution can also be realized by embedding in a larger unitary system [8,30,31,32,33]. When only some part of Hilbert space is measured it appears as if the evolution is non-unitary.…”
Section: A Lossy Single Kraus Operator Non-unitary Evolutionmentioning
confidence: 99%
See 1 more Smart Citation